Influence of trace element supplementation on anaerobic digestion of chicken manure: Linking process stability to methanogenic population dynamics - ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2018)
The effect of trace elements supplementation in anaerobic digestion of chicken manure (CM) and their influence on methanogenic population dynamics were assessed at total ammonia nitrogen (TAN) concentrations as high as 5000?mg/L for 332 days. With addition of selenium (Se), the CH4 yield increased 50% and reached to 0.27?+/-?0.01?L/g of volatile solids (VS) added. The results of metagenomic analysis showed that Se supplementation improved the digestion stability and CH4 production by increasing the activity and number of hydrogenotrophic Methanoculleus bourgensis. Due to the deficiency of trace elements other than Se, in course of time the CH4 yield decreased and dropped to 0.13?L/g of VS added. After starting to add a trace element mix containing cobalt (Co), nickel (Ni), molybdenum (Mo), tungsten (W) and Se, another hydrogenotrophic methanogen, Methanobrevibacter became dominant in the digester. Accordingly, along with the conversion of propionate to acetate and consumption of acetate via syntrophic acetate oxidation, the CH4 yield increased and reached to steady state at 0.32 +/- 0.01 L/g of VS added. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Ammonium; Chicken manure; Methanogens; Syntrophic acetate oxidation; Trace elements; SYNTROPHIC ACETATE OXIDATION; BIOGAS PRODUCTION; POULTRY LITTER; SYNTROPHOBACTER-FUMAROXIDANS; GENOME SEQUENCE; AMMONIA; SUBSTRATE; IMPACT; ENERGY; QUANTIFICATION